STYLISTIC FEATURES OF FASHION ADVERTISEMENTS - Abdug’afarova Aziza (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This paper dissects the socio-linguistic and stylistic elements within the advertisement of fashion, how language is optimally employed with the express goal of persuading, entertaining, and ultimately molding consumer behavior. A detailed analysis of rhetorical devices and persuasive resources available, these processes are expounded with a view to enhancing knowledge regarding the contribution of various forms of language to branding and promotion. By packing linguistic findings into the discourse of fashion advertisement, the paper offers an insight into how semiotics, intertextuality, and multilingual features contribute to the effectiveness of such advertisements. Besides, emotion, syntactic framework conditions, and metaphorical language are discussed in relevance to consumer engagement and brand perceptions.